Respuesta de proteínas séricas, enzimas hepáticas y electrolitos en juveniles de tilapia roja (Oreochromis mossambicus x Oreochromis niloticus) con inclusión de β-glucano en dieta - Zambrano Parrales, Mirella Aracely (2021)
This work was developed with the objective of evaluating the response of serum proteins, liver enzymes and electrolytes in juvenile red tilapia (Oreochromis mossambicus x Oreochromis niloticus) with inclusion of β-glucan in the diet. A completely randomized design (DCA) was applied under controlled conditions with a total of 6 treatments (0, 1, 2, 3, 4 and 5% inclusion ß-glucan in diet) with three repetitions (plastic aquariums). 15 fish / aquariums were stocked in 18 aquariums with a capacity of 90 L, for a total of 270 juveniles. According to the variables evaluated, the following results were obtained; for total proteins the best treatment (p ˂ 0.05) was T6 (19.00 g / dL), in T5 albumin (2.16 g / dL), for T6 globulin (16.92 g / dL). In the albumin / globulin ratio T1 and T2 including β-glucan, they showed less statistical significance for albumin. In calcium content, T4 showed a better response (p ˂ 0.05) with 1.26 mmol / L, for potassium (p ˂ 0.05) it was in T3 with 4.38 mmol / L. Significance (p ˂ 0.05) was also found for the variable urea with the T5 corresponding to 20.33 mg / dL, in enzymes such as T6 phosphatase 68.33U / L, in terms of TGP T5 149.67 U / L showing statistical significance. From the results obtained, it was found that ß-glucan in the diet improves the response of serum proteins, liver enzymes and electrolytes in juvenile red tilapia. Key words: Alanine amino transferase, blood chemistry, biostimulants, alkaline phosphatase, nutrition, potas